Unsteady blood flow in the stenosed artery subjected to magnetic field and injected nanoparticles - Jamil, Dzuliana Fatin (2018)
The blood flow in the stenosed artery was investigated in the current work. The blood, which was modelled as Newtonian or non-Newtonian fluid, was subjected to an oscillating pressure gradient and a periodic body acceleration. In the first problem, the magnetic field and the porosity were considered. In the second problem, the augmentation of heat transfer due to drug carriers such as nanoparticles (Fe3O4, TiO2, Cu) was modelled. In the first problem, the non-dimensional equation was solved by combining both perturbation and power series methods. However, for the second problem, only the perturbation method was used. The MATHCAD software was adopted to find the numerical figures of the analytical solutions. The presence of magnetic field tended to decelerate the blood flow in the stenosed artery due to strong resistance. However, the blood velocity increased with respect to the body acceleration, the pressure gradient and the permeability parameter. For the second problem, it was observed that the velocity increased with respect to the slip velocity and the body acceleration but decreased as the yield stress and the pressure gradient increased. The temperature of blood mixed with Fe3O4 was higher as compared to those with TiO2 and Cu nanoparticles, thus implying that Fe3O4 could be used as a diagnosis tool for drug delivery in stenosis treatment. The blood temperature increased slightly along the stream wise direction before reaching the constricted region. The temperature distributions were significantly dependent on periodic body acceleration, pressure gradient and Prandtl number.